ENHANCING GRADE VIII STUDENTS’ ENGLISH SPEAKING SKILLS THROUGH ROLE PLAY - Jelita Dian Pertiwi Panjaitan (Lingua Pedagogia, 2022)
This action research was aimed to enhance the speaking skills of grade VIII students at a junior public school in Yogyakarta through the role play in the academic year of 2020/2021. The research was conducted in two cycles with three meetings in each cycle. The research subjects were 34 students of grade VIII D of the school. The steps in this research were reconnaissance, planning, action and observation, and reflection. The data were collected through observation, interviews, a pre-test, a progress test, and post-test. The results of the research showed that there was an enhancement of the students’ speaking skills through the use of the role play. Besides, they also enhanced their confidence to speak in English since they had a lot of chances to practice role play. The analysis of the qualitative data, the enhancement can be seen from the students’ pronunciation, grammar, vocabulary, and fluency and there are improvement of students’ confidence and enthusiasm. Meanwhile, the analysis of the quantitative data, the enhancements could be seen from the scores of pre-test and post-test. The result showed that the mean score of the students’ speaking performance increased from 60.55 to 79.11 in the post test. The gain score of the students’ speaking skills was 1.9. The use of role play technique in enhancing English speaking skills proved that an opportunity to more practice is the key of role play which influenced in the enhancement of the students’ English speaking skills.